Prebiotics and β-Glucan as gut modifier feed additives in modulation of growth performance, protein utilization status and dry matter and lactose digestibility in weanling pigs - Hayhoe, Mychal-Ann Natalie; Archbold, Tania; Wang, Qi; Yang, Xiaojian; Fan, Ming Z. (Frontiers in Animal Science, 2022)
There are growing interests in developing novel gut modifier feed additives and alternative therapeutics to replace antimicrobials to enhance efficiency of nutrient utilization and to address the antimicrobial resistance threat to public health facing the global pork production. Biological mechanisms of supplementing lactose for enhancing weanling pig growth and nitrogen utilization are unclear. Thus, this study was prompted to determine effects of dietary supplementation of 3 prebiotics and oat β-glucan vs. a sub-therapeutic antibiotic on growth performance, whole-body protein utilization status, the apparent total tract dry matter (DM) and lactose digestibility in weanling pigs fed corn and soybean meal (SBM)-based diets. Six experimental diets were formulated with corn (40%), SBM (28%) and supplemented with dried whey powder (20%) and fish meal (9%) with titanium oxide (0.30%) as the digestibility marker. Diet 1 (NC, negative control), as the basal diet, contained no antibiotics and no supplemental prebiotics or β-glucan. Diet 2 (PC, positive control), contained an antibiotic premix (Lincomix-44 at 0.10%) in the basal diet at the expense of cornstarch. Diets 3, 5 and 6 contained 0.75% of the three test prebiotics of retrograded cornstarch (Diet 3), Fibersol-2 (Diet 5, a modified digestion-resistant maltodextrin) and inulin (Diet 6), and the viscous soluble fiber oat β-glucan (Diet 4), respectively, at the expense of cornstarch. A total of 144 Yorkshire pigs, at the age of 21 days (d) and an average body weight (BW) of 5.5 kg, were allocated to 12 floor pens with 3 barrows and 3 gilts per pen, and fed one of the 6 diets for 21 d in 2 study blocks according to a completely randomized block design. Initial and final pig BW, average daily gain (ADG), average daily feed intake (ADFI), representative pig plasma urea concentration as well as the apparent total tract DM and lactose digestibility during d 8-15 were measured. Analyses of variances, Dunnett’s and Tukey’s tests were conducted on the endpoints by using the SAS mixed model. There were no differences (P > 0.05) in ADG, ADFI, feed to gain ratio, plasma urea concentration, the apparent total tract apparent DM and lactose digestibility and the predicted whole-gut lactase digestive capacity among the diets, as examined by the Tukey’s test. There were no differences (P > 0.05) in these endpoints between each of the four treatment diets and the NC or the PC diet as examined by the Dunnett’s test. The total tract lactose digestibility was determined to be at 100%. The predicted whole-gut lactase digestive capacity was about eight times of the daily lactose intake when dietary lactose contents were supplemented at 10 - 12% (as-fed basis). In conclusion, dietary supplementation (at 0.75%) of the prebiotics and the oat β-glucan did not significantly affect the major growth performance endpoints, whole-body protein utilization status as well as the apparent total tract DM and lactose digestibility in the weanling pigs fed the corn and SBM-based diets. The promoting effect for growth and nitrogen utilization associated with dietary supplementation of lactose is due to the fact that lactose is a completely and rapidly digestible sugar rather than acting as an effective prebiotic in weanling pig nutrition.